Answer:
We have the function, ![f(x)=(x+3)^{2}-4](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B3%29%5E%7B2%7D-4)
On simplifying, we get,
![f(x)=x^2+6x+9-4](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%2B6x%2B9-4)
i.e. ![f(x)=x^2+6x+5](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E2%2B6x%2B5)
Thus, the standard form of the function is
.
Now, the factors of the given functions are (x+1) and (x+5).
<em>Since, the intercept form of the function is the factored form of the function.</em>
So, we have, intercept form of the function is
.
Now, we know that,
Value of x-coordinate of the vertex is
i.e.
i.e.
i.e. x= -3
Then,
i.e.
i.e. f(-3)=-4
So, the vertex of the function is (-3,-4).
Further, we know that,<em> 'the y-intercept of a function is the point where the function crosses y-axis'.</em>
So, when x=0, we have,
i.e. f(0) = 5
Thus, the y-intercept is (0,5)
Also, <em>'the x-intercept of a function is the point where the function crossese x-axis'.</em>
Then, for f(x)=0, we have
i.e.
i.e. x= -1 and x= -5
Thus, the x-intercept are (-1,0) and (-5,0).